Numerically Efficient Average-Value Model for Voltage-Source Converters in Nodal-Based Programs - SEYYEDMILAD EBRAHIMI; Taleb Vahabzadeh; Juri Jatskevich (IEEE Open Journal of Power Electronics)
Discrete detailed models of high-frequency switching voltage source converters (VSCs) are accurate but computationally expensive in simulations of large power-electronics-based systems. For fast/efficient studies, the average-value models (AVMs) of VSCs have proven indispensable, which conventionally utilize controlled voltage/current sources to interface with external circuits. In nodal-analysis-based electromagnetic transient (EMT) simulation programs with a non-iterative solution, the interfacing variables are computed based on the values of input voltages/currents calculated at the previous time step. This delay may cause numerical inaccuracy and/or instability at large simulation time steps. Recently, a so-called directly-interfaced AVM (DI-AVM) has been developed for VSCs that avoids this delay. In this article, the formulation of the DI-AVM is generalized for an arbitrary configuration of the interfacing nodes. This is done by formulating the extended equivalent conductance matrix for the VSC AVM, assuming all nodes are floating. The generalized conductance matrix is then merged into the overall network nodal equation. The extended DI-AVM is verified in PSCAD/EMTDC against the traditional dependent-source-based AVMs under both balanced and unbalanced conditions and is demonstrated to outperform the conventional AVMs in terms of numerical accuracy at large time steps.